Islamic Aptitude Testing and Student Talent Development in Islamic Education: Evidence from an Indonesian Islamic Secondary School - Mhd. Aksaril Huda Ritonga; Aulia Tegar Wicaksono; Nurti Budiyanti; Nadzifah Nadzifah; Muhamad Ma’sum (Jurnal Ilmiah Iqra', 2026)
The implementation of Islamic Religious Education in international schools is challenged by the limited use of diagnostic assessments capable of capturing students’ diverse levels of religiosity to support personalized learning. This study investigates the implementation of the Islamic Aptitude Test (IAT) at Darul Hikam International Secondary School and examines its implications for developing students’ religious potential in Islamic Religious Education. Adopting a qualitative case study design, data were collected through in-depth interviews, classroom and religious activity observations, and analysis of IAT-related documents. The findings demonstrate that the IAT effectively maps students’ initial competencies in faith, worship practices, moral conduct, Quranic literacy, and spiritual readiness, thereby enabling differentiated instruction and targeted religious mentoring. This study underscores the significance of the IAT as an integrative pedagogical framework that enhances adaptive, needs-oriented Islamic education and contributes to the development of systematic religious assessment models within international education contexts.